1998
DOI: 10.1001/jama.279.7.535
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Breast Cancer in Women

Abstract: Objective.-To assess the risk of invasive breast cancer associated with total and beverage-specific alcohol consumption and to evaluate whether dietary and nondietary factors modify the association. Data Sources.-We included in these analyses 6 prospective studies that had at least 200 incident breast cancer cases, assessed long-term intake of food and nutrients, and used a validated diet assessment instrument. The studies were conducted in Canada, the Netherlands, Sweden, and the United States. Alcohol intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 769 publications
(144 citation statements)
references
References 72 publications
10
132
1
1
Order By: Relevance
“…Non-differential misclassification could, therefore, be the reason that alcohol abuse was not a significant risk factor in this cohort, in contrast to studies of females with alcohol abuse (Smith-Warner, 1998). Similarly, unspecified alcohol/drug abuse was not a risk factor in this cohort.…”
Section: Discussioncontrasting
confidence: 74%
“…Non-differential misclassification could, therefore, be the reason that alcohol abuse was not a significant risk factor in this cohort, in contrast to studies of females with alcohol abuse (Smith-Warner, 1998). Similarly, unspecified alcohol/drug abuse was not a risk factor in this cohort.…”
Section: Discussioncontrasting
confidence: 74%
“…Postmenopausal women who drink alcohol may have increased serum estrogen levels, further increasing the plausibility of gender differences in the medical risks of drinking. [53][54][55] Acute increases in estrogen levels, up to threefold higher than baseline, have been observed after alcohol ingestion among postmenopausal women taking estrogen replacement. 56 This acute effect was not observed in postmenopausal women not taking estrogen replacement.…”
Section: Biological Plausibility Of Gender Differencesmentioning
confidence: 99%
“…56 However, some studies of non-estrogen-using postmenopausal women have observed increased estrogen levels in drinkers compared with abstainers, suggesting that chronic alcohol use may also be associated with increased estrogen levels. 53,55 For these reasons, increased estrogen levels associated with alcohol use may contribute to some of the observed relationship between alcohol and health in older women.…”
Section: Biological Plausibility Of Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies agree that there is a positive correlation between ethanol intake and the risk of breast cancer (see review by Hiatt, 1990;Plant, 1992;Rosenberg et al, 1993;Longnecker, 1994;Singletary and Gapstur, 2001). In general, studies show that risk is directly correlated with the duration of drinking, that is, the greater the total number of years drinking, the greater the risk (Bowlin et al, 1997;Swanson et al, 1997;Smith-Warner et al, 1998;Kuper et al, 2000). Furthermore, epidemiological data indicate that alcohol consumption is associated with advanced and invasive breast tumors (Weiss et al, 1996;Vaeth and Schlessinger, 1998).…”
Section: Introductionmentioning
confidence: 99%